2022
DOI: 10.1038/s41467-022-28980-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid age-grading and species identification of natural mosquitoes for malaria surveillance

Abstract: The malaria parasite, which is transmitted by several Anopheles mosquito species, requires more time to reach its human-transmissible stage than the average lifespan of mosquito vectors. Monitoring the species-specific age structure of mosquito populations is critical to evaluating the impact of vector control interventions on malaria risk. We present a rapid, cost-effective surveillance method based on deep learning of mid-infrared spectra of mosquito cuticle that simultaneously identifies the species and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 33 publications
2
78
0
Order By: Relevance
“…The cycle of seeking, digesting, and egg-laying is continued during their entire life span, and mosquito death is modeled as an age-dependent function. With these parameters we could model stable mosquito population dynamics (Figure 1A) that matches the age-distribution of mosquitoes observed in field settings 25 (Figure S1).…”
Section: Rare Long-lived Mosquitoes Transmit Malaria Parasitesmentioning
confidence: 64%
See 1 more Smart Citation
“…The cycle of seeking, digesting, and egg-laying is continued during their entire life span, and mosquito death is modeled as an age-dependent function. With these parameters we could model stable mosquito population dynamics (Figure 1A) that matches the age-distribution of mosquitoes observed in field settings 25 (Figure S1).…”
Section: Rare Long-lived Mosquitoes Transmit Malaria Parasitesmentioning
confidence: 64%
“…However, the age distribution of our simulated mosquito populations is remarkably similar to wild An . coluzzi mosquitoes, as recently measured with novel age-grading methods 25 . Like in our simulations, these natural mosquito populations have a very small proportion of old individuals (>17 days) that feed frequently (> 4 blood meals).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with Siria et al . [10], where CNN underperformed as a result of the difference in data distribution between the training and evaluation data driven by non-genetic factors such as ecological variation. When near-infrared spectroscopy was used to predict the age of Anopheles mosquitoes reared from wild populations, a similar limitation was reported [8,29].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that spectroscopic analysis of mosquitoes using near infrared (12500 – 4000 cm -1 ) or mid-infrared (MIR) (4000 – 400 cm -1 ) frequencies can identify key biochemical signals that vary with age [8,9]. These methods, when combined with specific machine learning (ML) techniques, allow for rapid estimation of mosquito ages [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation